Withholding and Withdrawal of Life-Sustaining Treatments in critically ill ICU patients: A study on attitude of Physicians of Bangladesh - Faruq, Mohammad Omar; Nooruzzaman, ARM; Tamanna, Rownak Jahan; Sultana, Amina; Mallick, Uzzwal Kumar; Asaduzzaman, Mohammad; Islam, Mohammad Motiul; Islam, Md Sirajul; Khanam, Rawshan Arra; Habib, Samira Humaira; Choudhury, Ashiq Haider (Bangladesh Critical Care Journal, 2019)
Background : This study is a sub analysis of data submitted on behalf of Bangladesh in an International study ( ACME 2012) involving physicians working in Asian ICUs. Objective : To describe attitude of physicians of ICUs of Bangladesh toward withholding and withdrawal of life sustaining treatments in end of life care, to assess factors associated with these observations and to compare the findings especially with those of physicians of low – middle income Asian ICUs. Method : Self-administered pre-set structured and scenario based survey conducted among 101 physicians working in 38 ICUs of Bangladesh. Results : For patients with no real chance of recovering a meaningful life, 20 of 101 respondents reported that they almost always or often withheld life-sustaining treatments and 18 of 101 respondents almost always or often withdrew life-sustaining treatments.44 respondents in our study reported that they almost always or often withheld life sustaining treatments whereas 10 respondents almost always or often withdrew life sustaining treatments. 72% of all our respondents would implement DNR orders. In Bangladesh, religion (Islam) does not influence decision of complying with DNR order requested by family. Our study showed 71% of physicians were more likely to “do everything” if a patient with hypoxic-ischaemic encephalopathy developed septic shock. In our study, physicians were more ready to withdraw vasopressors and hemo dialysis than enteral feeding and intravenous fluids. Physicians from Bangladesh generally perceived more legal risk with limitation of life sustaining treatments because of lack of legislation for such practices. When it comes to limit aggressive lifesaving treatments, Bangladeshi physicians were less likely accede to families request to withdraw them on financial ground. Conclusion : Like physicians of low-middle income countries of Asia, Bangladeshi ICU physicians’ self-reported practice of limiting life sustaining treatments, role of families and surrogates and perception of legal rights were significantly different than physicians of high income countries of Asia. However unlike physicians from other low income Asian countries, physicians from Bangladesh were less likely to accede to families request to withdraw life sustaining treatments on financial ground. Bangladesh Crit Care J September 2019; 7(2): 66-72